Science Reasoning: A Review and Bibliometric Analysis - Ina Ana Khoeriah; Irvan Permana; Didit Ardianto (Postgraduate, University of Mataram, 2022)
Improving critical thinking in science classes can be accomplished by developing reasoning thinking approaches. The goal of studying science reasoning in science classes is to see how much of this strategy is used in solving science problems and developing Higher Order Thinking Skills (HOTS) that are based on critical thinking. Between 2015 and 2021, a total of 100 articles were retrieved from the Google Scholar database and the Publishing or Perish (PoP) program. Mendeley desktop, a referencing management software, was then used to handle the selected references. Once the database was handled, this research employed VOS viewer software to categorize and visualize it. In general, this study provides a solid foundation for further research into